Unveiling BIM Value from Subcontractors’ Perspectives in The Malaysian Construction Industry - Mohd Noh, Nur Izzah; Tan Hui Min; Peniel Ang Soon Ern (International Journal of Sustainable Construction Engineering and Technology, 2025)
Building Information Modelling (BIM) has evolved as a strategic digital tool for enhancing collaboration and productivity in construction projects. While its adoption is steadily gaining momentum among main contractors, uptake among subcontractors, particularly small to medium-sized enterprises (SME), remains restricted due to contextual, organizational and technological constraints. This study assesses the subcontractors’ perceptions of BIM’s value and implementation challenges in Selangor, Malaysia. A structured quantitative survey was administered across G3 to G7 classified subcontractors as issued by the Construction Industry Development Board (CIDB) Malaysia, resulting in a response rate of 36.59. The findings reveal a relatively high level of awareness of BIM’s benefits, particularly in enhancing 3D project visualization (Mean = 4.53) and facilitating the integration of design and construction processes (Mean = 4.30). Nevertheless, critical barriers persist, led by the ‘Lack of clear direction for BIM implementation’ (Mean = 4.13), ‘Reluctance to initiate new operational workflows’ (Mean = 4.10) and ‘Inadequate team competency’ (Mean =4.07). Overall, the results suggest that in order to overcome arising BIM challenges, comprehensive policy reform, targeted capacity-building training and stronger top-down mandates from project stakeholders and regulatory bodies are needed. These insights contribute to the valuable formulation of strategic interventions which capable of fostering inclusive digital transformation within the Malaysian construction sector.